(3GdfhGRd GdLOjOI GdcHQis - (3eMeO GdegOj Hf eMeO Hf eMeO Hf NVQ Hf bGSe GdYeQGfj GdhRGfj GdaGSj, CHh YjSi,J (B1342 (3g` s
(3ChdgG (B:s
(3jHOC HfhGRd GdfcGM s
(3BNQgG (B:s
(3hGddg CYde GfJgi GdLRA GdKGfi hjdjg GdKGdK HYhf Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B114s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs